2008
DOI: 10.1111/j.1464-0597.2008.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

From Theory to Intervention: Mapping Theoretically Derived Behavioural Determinants to Behaviour Change Techniques

Abstract: Theory provides a helpful basis for designing interventions to change behaviour but offers little guidance on how to do this. This paper aims to illustrate methods for developing an extensive list of behaviour change techniques (with definitions) and for linking techniques to theoretical constructs. A list of techniques and definitions was generated from techniques published in two systematic reviews, supplemented by "brainstorming" and a systematic search of nine textbooks used in training applied psychologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
1,561
1
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,500 publications
(1,579 citation statements)
references
References 20 publications
8
1,561
1
9
Order By: Relevance
“…Hierarchical Cluster Analysis (HCA), the optimal number of groupings (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were examined for suitability using measures of Internal Validity (Dunn's Index) and Stability (Figure of Merit, FOM) [34]. Bootstrap methods were used in conjunction with the HCA, whereby data were resampled 10,000 times, to identify which groupings were strongly supported by the data.…”
Section: : Investigating Hierarchical Structure Of the Bct Listmentioning
confidence: 99%
See 2 more Smart Citations
“…Hierarchical Cluster Analysis (HCA), the optimal number of groupings (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were examined for suitability using measures of Internal Validity (Dunn's Index) and Stability (Figure of Merit, FOM) [34]. Bootstrap methods were used in conjunction with the HCA, whereby data were resampled 10,000 times, to identify which groupings were strongly supported by the data.…”
Section: : Investigating Hierarchical Structure Of the Bct Listmentioning
confidence: 99%
“…Historically it has often been concluded that how behavior change techniques are delivered may have as great or larger impact on outcomes as the techniques themselves [49]. Dimensions of behavior change interventions other than content, such as mode and context of delivery [5] and competence of those delivering the intervention [25,26] would thus also benefit from being specified by detailed taxonomies.…”
Section: Future Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve domains, including knowledge and skills, motivational factors, learning context, beliefs about capabilities, and the perceived role of the learner (Michie et al, 2005) map on to existing constructs from the research literature (Fishbein, Triandis, Kanfer, Becker, & Middlestadt, 2001). These domains can also be used to develop behavior change techniques (Michie, Johnston, Francis, Hardeman, & Eccles, 2008), and applying them to nurse education in pain management may enable better distinction of helpful from unhelpful findings and guiding theory (Gunnarsdóttir & Gretarsdottir, 2011;Twycross, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This approach appears to be successful in encouraging students to stay in school for lunch and is in agreement with the observation of Webb et al (59) that interventions incorporating more behaviour change techniques have a higher probability of being effective. The behavioural change methods applied in the present programme were selected mainly from those suggested by health and clinical psychologists with expertise in developing and implementing behaviour change interventions (26)(27)(28)67) .…”
Section: Discussionmentioning
confidence: 99%